Arterial elastic properties and central aortic pressure in patients with ankylosing spondylitis - T. A. Aksenova; N. F. Ivashchenko; V. V. Gorbunov; S. Yu. Tsarenok (Научно-практическая ревматология, 2019)
In recent years, arterial stiffness has been shown to be increased in ankylosing spondylitis (AS). However, this issue has not been sufficiently studied today.Objective: to investigate central aortic pressure values and pulse wave velocity (PWV) in patients with AS and their relationship to the clinical manifestations of the disease.Subjects and methods. A total of 47 patients (mean age 37.0+10.1) with AS were examined. ASDAS-CRP averaged 3.2+0.9; the duration of AS was 6.0+4.6 years; and the radiographic stage of sacroiliitis was 2.3+1.4. A control group included 33 healthy individuals. The groups were matched for age, gender, and office blood pressure (BP). Central aortic pressure and PWV were determined by applanation tonometry on a SphygmoCor apparatus (AtCorMedical, Australia). The Mann-Whitney U test and the Spearman correlation coefficient test were used for statistical analysis.Results and discussion. In the patients with AS, central systolic and diastolic BP was significantly higher than that in the controls (115.4+14.04 and 101.1 + 10.2 mm Hg, p=0.00001 and 78.6+12.3 and 71.8+7.3 mm Hg respectively, p=0.001). The patients with AS showed a 15.01% increase in mean central aortic pressure values compared to the control group (106.5+13.7 and 92.6+9.4 mm Hg, respectively; p=0.0001). Carotid-femoral PWV averaged 6.6+1.7 m/sec in the patients with AS and 5.20+0.96 m/sec in the controls (p=0.0001). There was a direct correlation of PWV with the occiput-wall distance r= 0.36; p=0.01) and an inverse correlation with Schober's test (r=-0.54; p=0.0001).Conclusion. The patients with AS were found to have increased arterial stiffness parameters, such as PWV, central aortic pressure, central diastolic BP, and central hemodynamic pressure. PWV was demonstrated to be related to clinical data.